Synthesis of graphitization control system of carbon products - Жученко, Олексій Анатолійович; Бевзюк, Леонід Леонідович (Technology audit and production reserves, 2016)
Current global trends in ferrous and nonferrous metallurgy, machine building, chemical and other industries cause a permanent increase of production of carbon graphite products. Production of graphite products is complex, multistage and very energy-intensive. The analysis of existing graphitization control systems of carbon products has shown that these systems are the systems of program control that do not take into account the current state of the control object, which affects their performance. A new control system provides graphitization furnace control in two modes of operation – heating and graphitization. The framework of control system in heating mode is based on the use of fuzzy controller, which inputs are calculated using a simplified model of graphitization. The control algorithm in graphitization mode for the purpose of determining in advance the time of power outage of the furnace uses prediction of graphitization degree of carbon products.